#AMIRetreat2017 International Conference - Panos, Dionysis (My University, 2026)
"#AMIRetreat2017 - Journalism, Society and Politics in the Digital Media Era" International conference organized by the Advanced Media Institute, the Open University (Cyprus), the Centre for the Study of Journalism, Culture and Community at Bournemouth University (UK), and the Laboratory of Research in New Economy and Development at University Hassan II Casablanca (Morocco), with the support of the Dpt. of Communication & Internet Studies of the Cyprus University of Technology at the premises of which the conference was hosted. Participants from 45 different countries worldwide followed 21 different thematic panels and 3 key-note speakers: Nico Carpentier (Uppsala University), Paul Michaelides (Emerson University, Boston, USA) and Nicos Christodoulidis (Government Spokesman).